THE SOCIO-ECONOMIC EXPLANATION OF TURKISH POLITICS (Third Sector Social Economic Review, 2015)
In this study, starting from 1908, Turkish politics is analyzed in socio-economic context . The socio-economic change is evaluated within political dimensions of historical platform. Consequently, since the period of the Committee of Union and Progress in Turkey, the effort in creation of a bourgeois class with the help of the state by implementing a top-down method has been traced back. However, since Özal, as a result of liberalisation in economy, politics and society, the emergence of a bottom-up bourgeois class has been observed. By analyzing recent developments, the bottom-up bourgeois class has taken power and has been increasingly becoming strong in economic area. Whereas the old bourgeois can not keep up with the recent change and they have been found to lose strength firstly but not only in political sphere but also in social and economic fields.
Keywords: Turkish Politics; Socio-economic change; Bourgeois; Civil Society; Democracy